From Decree 43810-MGP to Decree 44501-MGP: A chaotic transition and some persistent doubts in the protection of the rights of refugees in Costa Rica - Abarca Sánchez, Jesús Andrés (2025)
A brief historical overview is provided to explain the high number of over 200.000 asylum applications awaiting resolution by the Costa Rican State. (...)